Transcending computational limits: A first-principles analytical framework for energy and exergy performance in nanofluid-based direct absorption solar collectors - Alabas Hasan; Anas Alazzam; Eiyad Abu-Nada (Case Studies in Thermal Engineering)
A novel analytical framework is presented for the comprehensive energy and exergy evaluation of nanofluid-based direct absorption solar collectors (DASCs), delivering a closed-form solution under established assumptions of plug flow and constant optical properties. Significantly, this research extends the analytical framework to conduct a second-law thermodynamic evaluation of system performance. Key operational and design parameters, such as the Nusselt number, collector geometry, and nanoparticle loading and material type, were systematically analyzed to ascertain their impact on critical performance indicators, including temperature distribution, and absorption, thermal, and exergetic efficiencies. Model validity is robustly confirmed through benchmarking against experimental, numerical, and analytical datasets, utilizing a simplified optical model where scattering effects are justifiably omitted for ultrafine nanoparticles (≤ 30 nm). Findings reveal the DASC's superior thermal management via internal peak temperature trapping within the bulk fluid, a direct consequence of volumetric absorption, which significantly curtails top surface heat losses and enhances overall efficiency. The model delineates optimal operational strategies for achieving this internal temperature confinement. Moreover, a comparative study of nanoparticle materials demonstrates a crucial decoupling between optimal solar absorption and maximal thermal/exergetic efficiencies. The model also predicts an absorption saturation effect beyond a critical nanoparticle concentration, potentially diminishing collector thermal and exergetic performance.